Correlation of Hemoglobin Levels with Nutritional Status in Adolescent Girls: A Health Promotion Perspective - Sari, Rati Purnama; Silaban, Evi Maria Lestari; Merry, Yussie Ater (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2023)
Background: Women during pregnancy, childbearing age, and adolescents are prone to anemia. The prevalence of anemia in adolescents in Indonesia in 2018 reached 32%. The objectives of this study were to determine the correlation between nutritional status with the incidence of anemia in adolescent girls.Method: Describe briefly the main methods or treatments applied. This study is an analytical survey with a cross-sectional design. The population in this study was student girls in Padang City in 2022.The instrument used to measure hemoglobin was a digital Hb measuring instrument. The nutritional status in this study used the measurement of the nutritional status of adolescents with the indicator of BMI according to age. Correlative analytic test with ordinal scale data used the Kendall's tau test.Results: Based on the results of this study, was known that most of the 71.9% of adolescent girls whose nutritional status is normal. Most of the adolesce girls (87.5%) had normal hemoglobin levels, and as many as 12.5% adolensce girls had anemia who were not menstruating. Nutritional status (BMI/age) and hemoglobin levels were not correlated. Nutritional status is not a factor causing anemia in adolescent girls. It is necessary to investigate the prevalence of anemia in adolescent girls during menstruation as a comparison.